SIGNIFICANCE OF CYTOGENETIC ABNORMALITIES IN PATIENTS WITH POLYCYTHEMIA VERA - Sever, Matjaz (2013)
We analyzed 133 patients with polycythemia vera (PV) that were followed at our institution (median 7.5 years) and had adequate cytogenetic information. The 5-, 10-, and 15-year survival rates were 93%, 79%, and 64%, respectively, with the median projected overall survival of 24 years. Nineteen patients (14%) had abnormal cytogenetics at any time during the disease course (no survival difference). Sixteen patients (12%) transformed during follow up, after a median of 8.5 years, to myelofibrosis (11), acute myeloid leukemia (4), or myelodysplastic syndrome (1); 8 had cytogenetic abnormalities. Among 133 patients, 39 were newly diagnosed: 33 with normal and 6 with abnormal cytogenetics (no survival difference); 9 transformed (6 with normal and 3 with abnormal cytogenetics at diagnosis). In keeping with other smaller series, the presence of chromosomal abnormalities may have a role in the transformation of patients with PV; survival was not affected likely due to short follow up.